Histological comparison of the rhizome, leafy culm and aerial rhizome of the common reed (Phragmites australis) - Bankó, László (Acta Biologica Szegediensis, 2010)
In this study we focused on the morphology of an unusual organ, appeared on the culm of read (named as aerial rhizome), rhizome and leafy culm of the reed plant (Phragmites australis (Cav.) Trin. Ex Steudel). The aerial rhizome appeared on young reclined culms or at occasionally broken nodes of reed plants grown in a glasshouse, in perlite and nutrient solution. During the 5 years of cultivation, under greenhouse circumstances the plants remained small if their size is compared to that of the natural reed stands, but the segments developed into an interconnected, well-grown system of roots and leafy culms. According to the histological results, the structure of the aerial rhizome and rhizome revealed a great similarity. The resemblance is not only noticeable in the number of the cell-lines and size of the primary cortex and central cylinder but also in the existence of the lacunae and the central cavity. So far no information concerning the role of the aerial rhizome came to light in the literature; according to our best knowledge, similar structure has not even been mentioned. It is tempting to speculate that the structure’s main role may be the vegetative reproduction, horizontal spread of the clone, since histologically greatly resembles to the rhizome. We hypothesize that the structure develops under extreme conditions, e.g. continuous stress such as growing the plants in spatial constrains which cannot be found in natural conditions. Consequently, the cause of the formation of the structure can originate from the extremism of the living-conditions.